Perception on challenges impacting bid decision of indigenous building contractors in Dar Es Salaam, Tanzania. Issue 6 (14th May 2020) - Chileshe, Nicholas; Edwards, David John; Kavishe, Neema; Haupt, Theo C.
Abstract : Purpose: The acknowledged mode of securing work by contractors is through the bidding process. However, the bidding decisions undertaken by some indigenous contractors in developing countries are fraught with challenges that often engender bidding practices (such as collusion through price fixing and intentional lower bidding) and threaten business survival. Therefore, in the quest to better understand these challenges and viable advocate solutions for overcoming them, this paper aims to identify the key challenges impacting the bid decision process by small indigenous building contractors in Dar es Salaam, Tanzania, and establish the strength of their relationship between the pairs of key challenges. Design/methodology/approach: A comprehensive literature review was conducted to identify nine challenges impacting the bid decision of indigenous building contractors in Tanzania, which were used to design a questionnaire survey. Data collected were analysed using descriptive statistics, mean score, inferential statistics (One sample t -tests), Kendall's concordance and correlation analysis. Findings: Challenges identified from a literature review were empirically tested using survey responses accrued from 33 participating small indigenous building contractors in Dar es Salaam, Tanzania. The findings illustrate that lack of liquidity, profit returns, lack of equipment, lack of experience of several works and procurement procedures are perceived as being the five most critical challenges. Project location, site accessibility and lack of labour were least critical. The major finding from the correlation analysis was the existence of the strong and positive correlation between "project location" and "site accessibility". Research limitations/implications: The study is limited by its sample and geographical settings which focussed and confined the results on one country, Tanzania. However, the findings can be considered as important for other developing countries wishing to gain insights into the challenges impacting bid decisions. Practical implications: Measures for addressing the identified challenges impacting the bidding decisions of the indigenous small building contractors would be undertaken. The findings will enable contractors to not only reconcile the challenges with the industry and in so doing benefit both themselves and the clients but also enable them to be better prepared to deliver contractual obligations and generate socio-economic wealth. Government and policymakers will also be able to appropriately develop macro interventions for managing these challenges, which could be custom-tailored to indigenous small contractors. Finally, improving the ability of local firms to compete in the construction industry has been recognised as having the potential of advancing socio-economic development within the comity of developing countries. Originality/value: The study enhances government, client and practitioners' understanding of the challenges affecting the bidding practices among the indigenous building contractors in Tanzania. This area of investigation has previously been under explored particularly sub-Saharan Africa.